Glutamate spillover drives robust all-or-none dendritic plateau potentials—an in silico investigation using models of striatal projection neurons - Trpevski, Daniel; Khodadadi, Zahra; Carannante, Ilaria; Hellgren Kotaleski, Jeanette (Frontiers in Cellular Neuroscience, 2023)
Plateau potentials are a critical feature of neuronal excitability, but their all-or-none behavior is not easily captured in modeling. In this study, we investigated models of plateau potentials in multi-compartment neuron models and found that including glutamate spillover provides robust all-or-none behavior. When glutamate spillover is not included, the all-or-none behavior is very sensitive to the steepness of the Mg block. These results suggest a potentially significant role of glutamate spillover in plateau potential generation, providing a mechanism for robust all-or-none behavior across a wide range of slopes of the Mg block curve. We also illustrate the importance of the all-or-none plateau potential behavior for nonlinear computation with regard to the nonlinear feature binding problem.